Drinking Over the Lifespan: Focus on Older Adults - Barry, Kristen L. (Alcohol Res, 2016)
A substantial and growing number of older adults misuse alcohol. The emerging literature on the “Baby Boom” cohort, which is now reaching older adulthood, indicates that they are continuing to use alcohol at a higher rate than previous older generations. The development and refinement of techniques to address these problems and provide early intervention services will be crucial to meeting the needs of this growing population. This review provides background on the extent of alcohol misuse among older adults, including the Baby Boom cohort that has reached age 65, the consequences of misuse, physiological changes related to alcohol use, guidelines for alcohol use, methods for screening and early interventions, and treatment outcomes.